2002
DOI: 10.1016/s1044-0305(02)00364-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed fluorescence measurements of trapped molecular ions with zero background detection

Abstract: Sensitive methods have been developed to measure laser-induced fluorescence from trapped ions by reducing the detection of background scattering to zero levels during the laser excitation pulse. The laser beam diameter has been reduced to ϳ150 m to eliminate scattering on trap apertures and the resulting laser-ion interaction is limited to a volume of ϳ10 Ϫ5 cm 3 which is ϳ0.03-0.15 of the total ion cloud volume depending on experimental conditions. The detection optics collected fluorescence only from within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…The absorption maximum ( max ) for rhodamine 575 in solution is reported by the manufacturer to be at 518 nm and is expected to blue shift in vacuum. Xanthene dyes have strong absorption blue shifts (ϳ30 nm) in vacuum [7,11]. Fluorescence measurements at 476-nm incident laser light were attempted, but not observed, because of the poor SNR caused by the low optical density of the notch filter below 488 nm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The absorption maximum ( max ) for rhodamine 575 in solution is reported by the manufacturer to be at 518 nm and is expected to blue shift in vacuum. Xanthene dyes have strong absorption blue shifts (ϳ30 nm) in vacuum [7,11]. Fluorescence measurements at 476-nm incident laser light were attempted, but not observed, because of the poor SNR caused by the low optical density of the notch filter below 488 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Because only a fraction of the ion cloud is thought to be irradiated at any one time by the laser beam (waist, 1 mm) and the ions are continuously moving into and out of the laser beam, the photodissociation rate will be affected by the relative time the ions spend inside and outside of the laser beam. Parks and colleagues [7] investigated the dependence of the fluorescence of trapped ions on the interaction volume, where the ions and laser beam overlap, and found that the photodissociation depends on the interaction volume, the irradiation time, and the laser intensity. Using their reported values, we expect a linear dependence on the fluorescence with the effective overlap of the laser with the ion cloud at constant trap parameter q z ϭ 0.24, …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations